Work-Cells Concept Development for High Mix Low Volume Market Conditions. (2015) - Karaulova, Tatyana; Shevtshenko, Eduard
Abstract: Work-cells implementation enables enterprises to increase simultaneously the flexibility and productivity measures of a production process. An elaboration model permits focusing on the required outputs of the project and controlling of the implementation process. The developed work-cells concept is supported by a similarity analysis, production line balancing, as well as a production process simulation, and is followed by the analysis of the achieved results. The authors expect that this paper can be used by enterprises as a practical guide for work-cells implementation.